Analisis Pengaruh Lingkungan Kerja dan Promosi Jabatan terhadap Kinerja Karyawan - Linda Triya Kristin Kusuma Dewi; Rofikul Amin (Jurnal Manajemen dan Kewirausahaan, 2016)
The purpose of this study is to understand and analize the affect of job promotion and work environment on employee performance. The population of this research are the employees of Royal ATK Malang. The sample in this study are 40 employees who work on Royal ATK Malang. The sample technique is a proportional random sampling. The method used in this research is multiple linear regression analysis. The result of F test indicates that job promotion and work enviroment affect on employee performance simultanly. Based on t test, job promotion and work enviroment has a significant affect on employee performance partially.work enviroment has a dominant affect on employee performance.https://doi.org/10.26905/jmdk.v4i2.497